Unveiling the dynamic interconnectedness of fossil fuels, clean energy, water, and technology assets - Melike Aktaş Bozkurt (Borsa Istanbul Review)
This study explores dynamic interconnectedness and volatility spillovers among four asset clusters—brown (fossil fuels), green (clean energy), blue (water-related), and orange (technology)—from April 2014 to October 2024, incorporating major geopolitical events, such as COVID-19, the Russia-Ukraine war, and the Israel-Gaza conflict. Using time-varying parameter–vector autoregressions and wavelet coherence, the analysis shows that green and blue clusters display higher resilience and lower spillovers under crisis conditions, suggesting their potential to act as safe havens. Meanwhile, the brown cluster faces heightened vulnerability to energy market shocks, and the orange cluster strengthens its ties with clean energy assets when driven by technological innovation. These findings highlight growing decoupling between clean energy and fossil fuels and the pivotal role of technology in accelerating that shift.